Gradiente ambiental e peixes de riachos de cabeceira da Mata Atlântica (SP) - Mello, Bruno José Gomes (2014)
The growing interest in studies of functional diversity allows to address the relationship between the functional characteristics of species with variations in the environment attempt to understand the organization of biological communities. We examined the relationship between physical and structural characteristics of 19 stretches of headwater streams in the Atlantic Forest and morphological characteristics related to swimming ability of fish species. The environment was described by altitude, distance from species pool, substrate composition and depth of the channel. The functional characteristics were described by 11 morphological measurements. The RLQ analysis was used and the first two axes explained 97.8% of the total variation. The first axis was interpreted as the action of the altitudinal/longitudinal gradient in the structuring of assemblies of fish which varied with morphological measurements of length of caudal fin and caudal peduncle. We can say that there are two distinct assemblies positioned at the extremes of the environmental gradient separated by capacity of swimming of the species. Within these groups we can say that on a local scale the physical structure of the channel generates subgroups related to the use of the niche, suggesting the action of environmental filters. Thus, we present evidence that environmental attributes of headwaters of the Atlantic Forest are related to the structure of the assemblies of fishes that inhabit these environments.